Association of the Vaccination Status of Health Workers of COVID-19 Survivors with The Outcomes of Treatment of COVID-19 At General Hospital in Padang City - Kornelis Aribowo; Masrul Basyar; Yessy Susanty Sabri (Jurnal Respirologi Indonesia, 2023)
Background: Health workers are on the front lines of treating and fighting the COVID-19 pandemic. Health workers face COVID-19 patients at work. Health workers are at increased risk of infection if they are not properly protected. Increased risk for health workers can be caused by contact with patients without personal protective equipment (PPE) and surfaces contaminated with the virus. Infected health workers can infect other people around them and will increase the workload of other health workers. One of the efforts to reduce the risk of transmission to health workers is vaccination. Vaccines against COVID-19 are considered very important to prevent and control COVID-19. The aim is to determine the relationship between the COVID-19 vaccine status and the outcomes of healthcare workers treated for confirmed COVID-19 at hospitals throughout Padang.Methods: This observational study was conducted using a retrospective cohort method. The study was conducted from August 2021 to May 2022 in hospitals across Padang by completing a questionnaire in the form of a Google form link. Results: Vaccination status of health workers who survived COVID-19 who were treated at Padang City General Hospital (66.97%) were not vaccinated, aged 26–35 years (57.80%), female (80.73%), worked as paramedics (63, 55%), symptom onset 3 to 7 days (44.95%), number of symptoms 3 (55.96%), most fever (24.68%), number of comorbid 1 to 2 (66.06%), obesity (66.67%), length of stay <21 days (84.40%), and mild clinical (55.96%) and recovered (92.66%). The highest degree of COVID-19 severity for health workers who were not vaccinated was moderate clinical, 42 samples (57.53%), and vaccinated, predominantly mild clinical, 34 samples (94.44%). The duration of stay of health workers vaccinated was higher than that who were not vaccinated (97.22% vs. 78.08%).Conclusion: The vaccination status of health workers who have survived COVID-19 relates to a clinical degree, length of stay, and outpatient treatment.